Identification of Off-Label Drugs for Patients with Neurological Disorders at the Psychiatric Hospital “Ghrasia” Yogyakarta - Bangunawati Rahajeng; Asih Ulandani; Astrit Ikafitriani (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2022)
Off-label drug use is the prescription of drugs outside the indications approved by the authorized agency. The reasons for off-label drug use include a lack of clinical response to previous treatments, intolerance, or contraindications to drug therapy. The scientific evidence of off-label prescribing was lacking, and the risk of adverse events increased. This study aims to identify the off-label drug use for patients with neurological disorders at the Psychiatric Hospital “Grhasia” Yogyakarta. This study used a descriptive observational design with a cross-sectional method. Data collection was conducted retrospectively. Sampling was carried out by using the purposive sampling technique. The sample was patients who received a psychotropic prescription at the Psychiatric Hospital “Grhasia” Yogyakarta in January-December 2019. The data were analyzed by scrutinizing the therapeutic goals according to the diagnosis on the medical record. Prescriptions not matching the indications registered by NADFC are included in the off-label category. We used descriptive analytics for demographic data, disease diagnosis, and frequency of the off-label use of drug in neurological disorders. The research obtained a total sample of 662 patients that met the inclusion criteria, with 2,823 psychiatric drugs used. The off-label use of drug in neurological disorders at the Psychiatric Hospital “Grhasia” Yogyakarta was 884 (31%). The most frequent off-label use was lorazepam (17.53%). This study concludes that there is an off-label prescription at the Psychiatric Hospital “Grhasia” Yogyakarta. Some of the off-label use has no solid scientific evidence. These results require further research regarding the reasons for off-label prescribing and the patient's safety.